Beiträge zur Insektenfauna der DDR: Lepidoptera - Pyraustinae. - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1980)
By evaluating previous publications and collections an by active and systematic collecting 61 species of Pyraustinae could be ascertained in the GDR. Three species were mentioned in publications but could not yet be confirmed. Diagrams of the flying periods of most species give a survey of the seasonal apperances of the species. Descriptions of the genital apparatures facilitate their determination.